2015
DOI: 10.1111/jtxs.12153
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Flour Dough Rheological Properties Measurement: Effects of the Target Values on the Attained Results

Abstract: Lubricated squeezing flow experiments on wheat flour dough have been performed in constant plate speed and constant extension rate modes. The objective of this work was to assess the effects of the target values on the attained results obtained during wheat dough rheological properties measurement. Different rheometers were used to allow these operations. In both cases, each constant target speed used increases with the increasing time before reaching its stability. These increasing effects versus time are hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
(61 reference statements)
1
0
0
Order By: Relevance
“…Our results are in agreement with previous studies (Singh and Singh 2013) which depicted that G 0 of dough from all the varieties was greater than G 00 , indicating predominance of elastic character. Similar results have been reported by Mohammed et al (2011) and Koussa-Koffi et al (2015) who studied the dynamic rheological properties of chickpea and wheat flour doughs and observed that storage modulus was greater than the loss modulus in all the wheat doughs, indicating viscoelastic and solid like behavior of all the doughs.…”
Section: Rheological Measurementssupporting
confidence: 90%
“…Our results are in agreement with previous studies (Singh and Singh 2013) which depicted that G 0 of dough from all the varieties was greater than G 00 , indicating predominance of elastic character. Similar results have been reported by Mohammed et al (2011) and Koussa-Koffi et al (2015) who studied the dynamic rheological properties of chickpea and wheat flour doughs and observed that storage modulus was greater than the loss modulus in all the wheat doughs, indicating viscoelastic and solid like behavior of all the doughs.…”
Section: Rheological Measurementssupporting
confidence: 90%